Frictional Behaviour and Surface Topography Evolution of DLC-Coated Biomedical Alloys - Nečas, David; Gelnar, Adam; Rothammer, Benedict; Marian, Max; Ranuša, Matúš; Wartzack, Sandro; Vrbka, Martin; Křupka, Ivan; Hartl, Martin (Biosurface and Biotribology, 2025)
Advanced engineering coatings offer a promising solution to enhance the longevity and performance of medical biomaterials in orthopaedic implants. This study hypothesises that diamond-like carbon (DLC) coatings exhibit distinct frictional performance based on substrate and counterface material. Three different DLC coatings were tested using a pin-on-plate test in four material combinations. Virgin and DLC-coated CoCrMo and Ti6Al4V pins were tested under sliding against UHMWPE and glass plates with simulated body fluid lubrication. Results revealed that coating composition significantly impacts frictional performance, with silicon- and oxygen-doped coatings showing great potential to minimise friction. Surprisingly, reducing contact pressure had either a neutral or somewhat negative effect. Future investigations will focus on long-term testing and lubrication analyses of these material combination
Keywords: Biotribolgy; CoCrMo; Diamond-like Carbon; Implant materials; Synovial joint; Ti6Al4V